The Role of Digital Marketing in Influencing Patient Interest to Visit Prodia Clinical Laboratory Through Corporate Image - Widodo, Djoko Setyo; Rachmawati, Dwi; Wijaya, Hadi; Dewi, Nur Fitri; Udriya, Udriya (Dinasti Publisher, 2024)
In the digital era, digital marketing strategies have become a key factor in influencing consumer behavior, including in healthcare services. Prodia Clinical Laboratory, as one of the leading laboratories, leverages digital marketing to enhance its corporate image and attract patient interest. This study aims to analyze the role of digital marketing in influencing patient interest in visiting Prodia Clinical Laboratory through corporate image. The research employs a quantitative method using surveys of Prodia’s patients and prospective patients. The results show that digital marketing has a positive and significant impact on patient interest, mediated by a strong corporate image. A positive corporate image plays a crucial role in building trust and increasing patients' decisions to choose Prodia. These findings suggest that Prodia should continue improving the quality of its digital marketing efforts to maintain and enhance its corporate image and attract more patients.